NOMS Workshops 2008 - IEEE Network Operations and Management Symposium Workshops 2008
DOI: 10.1109/nomsw.2007.25
|View full text |Cite
|
Sign up to set email alerts
|

Monitoring three National Research Networks for Eight Weeks: Observations and Implications

Abstract: Abstract-With the advent of dynamic and elusive distributed applications such as peer-to-peer file sharing systems, network administrators find it increasingly difficult to understand the types of applications running in their networks and the amount of traffic each application produces.In this paper, we present measurement results from the deployment of an accurate traffic characterization application in three National Research and Education Networks for a period of two months. Our observations go beyond traf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2011
2011
2011
2011

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 11 publications
0
1
0
Order By: Relevance
“…From Figure 3(b), we observe a uniform distribution of file hosting traffic during the week with a slight dip occurring on Sunday. These results show a deviation from the usual found Web usage to be diurnal in research and educational networks, though P2P did not exhibit such behaviour [2]. Gill et al found YouTube usage to be diurnal as well and found usage to be lower on weekends [11].…”
Section: Time Patternsmentioning
confidence: 65%
“…From Figure 3(b), we observe a uniform distribution of file hosting traffic during the week with a slight dip occurring on Sunday. These results show a deviation from the usual found Web usage to be diurnal in research and educational networks, though P2P did not exhibit such behaviour [2]. Gill et al found YouTube usage to be diurnal as well and found usage to be lower on weekends [11].…”
Section: Time Patternsmentioning
confidence: 65%